Maximal strength, power, gross efficiency and performance during isolated upper-body poling in cross-country skiers - Welde, B.; Hansen, M.; Ettema, G.; Sandbakk, O. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Previous studies have shown upper-body strength and power to associate with work economy/efficiency and endurance performance in various types of locomotion. This aspect has not yet been investigated for isolated upper-body work. The present study correlated gross efficiency (GE) and performance with maximal strength and power during isolated upper-body poling.